Ritual Kelas pada Suku Rakas Manggarai - Urak*, Monika Putri; Saffanah, Winin Maulidya (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The Kelas Ritual is one of the original cultures of the Manggarai community that is still conducted as a form of respect for their ancestors. "Kelas," which means "feast" in Indonesian, is an event or ceremony to bid farewell to the spirits/souls of the deceased. The souls of the departed are purified and saved through the Kelas ritual. The method used in this paper is a descriptive qualitative method. The author collected data through interviews, observations, and documentation. The research findings indicate that the Kelas Ritual among the Rakas tribe has stages or processes, starting from the post-death stage, core preparation, and closure (wali anak rona). The ritual holds significance as a sign of respect for the deceased. Based on the research results, the Rakas tribe believes that this ritual is a form of honoring and releasing the departed family members. Additionally, the ritual is believed to bring peace and prevent wandering spirits. The ritual involves the participation of relatives as a form of social solidarity within the Rakas community.